Sarcoidosis-like reaction induced by immune checkpoint inhibitors in patients with advanced melanoma: a report of two cases and a brief review of the literature - Dujović, Branko; Kandolf, Lidija; Radević, Tatjana; Petrov, Nenad; Mijušković, Željko (Vojnosanitetski pregled, 2025)
Introduction. Immunotherapy is associated with a wide range of adverse events. A drug-induced sarcoidosis-like reaction is a systemic granulomatous reaction that is no different from sarcoidosis and occurs in a certain temporal relationship with the initiation of the drug. Case report. The first presented patient was a 61-year-old male with stage IIIC BRAF-positive melanoma treated with adjuvant nivolumab therapy. After four cycles of therapy, enlarged mediastinal lymph nodes were confirmed using computed tomography. Bronchoscopy with bronchoalveolar lavage and transbronchial biopsy showed chronic granulomatous inflammation. After 12 cycles, grouped brownish-red papules and plaques covered with whitish scales were observed in the skin of both knees, and a histopathology finding indicated a sarcoidosis-like reaction. He was treated with oral prednisone, 60 mg daily in decreasing doses, and after 16 months, the enlarged mediastinal lymph nodes and skin lesions disappeared completely. The second presented patient was a 45-year-old male with stage IIIC BRAF-positive melanoma treated with adjuvant pembrolizumab therapy. After four cycles, enlarged mediastinal lymph nodes were observed. Bronchoscopy with bronchoalveolar lavage revealed granulomatous inflammation, and transbronchial biopsy confirmed sarcoidosis. Therapy with oral prednisone 40 mg daily in decreasing doses was performed in the next three months, and immunotherapy was continued. The enlarged mediastinal lymph nodes resolved after completion of adjuvant therapy. Conclusion. In most cases, a diagnosis of a sarcoidosis-like reaction requires a biopsy of the suspected lesions. It is not usually necessary to stop immunotherapy, but sometimes standard corticosteroid therapy is indicated. An interdisciplinary approach is important to distinguish true disease progression from adverse drug reaction.